Homotopy Method for a General Multiobjective Programming Problem - Song, W.; Yao, G. M. (Journal of optimization theory and applications, 2008)
In this paper, we present a combined homotopy interior-point method for a general multiobjective programming problem. The algorithm generated by this method associated to Karush–Kuhn–Tucker points of the multiobjective programming problem is proved to be globally convergent under some basic assumptions.